An evaluation of drug promotional literatures published in scientific medical journals - Pooja M Vachhani; Manish N Solanki; Mira K Desai (Wolters Kluwer Medknow Publications, 2016)
Objectives: Evaluation and comparison of ethical standards of published drug promotional literatures (DPLs) between different Indian and non-Indian scientific medical journals regarding compliance to the World Health Organization (WHO) and International Federation of Pharmaceutical Manufacturers and Associations (IFPMAs) guidelines. Materials and Methods: A cross-sectional, observational study was carried out at pharmacology department. DPLs published in Indian and non-Indian scientific medical journals available at central library of medical college during the period of 6 months were collected according to selection criteria. DPLs were evaluated and compared for compliance to ethical standards of drug promotion laid by the WHO and IFPMA. Data were analyzed using Fisher's exact test. Results: Out of total 178 DPLs, 103 DPLs were from Indian journals and 75 DPLs were from non-Indian journals. When compared regarding compliance to all the 11 ethical criteria of WHO, no significant difference was found between DPLs published in Indian and non-Indian journals. However, DPLs from indian journals contained significantly less information regarding dosage regimen (P = 0.0096), adverse drug reactions (P = 0.0028), warnings (P = 0.0104) and major drug interactions (P < 0.0001) as compared to non-Indian journals. Compliance to all the five IFPMA criteria was significantly higher in DPLs of non-Indian journals (88%) than Indian journals (39%) (P < 0.0001). Conclusion: Noncompliance to ethical standards of WHO and IFPMA guidelines is more common in DPLs of Indian journals as compared to non-Indian journals. Thus strict implementation of regulatory measures regarding DPLs published in Indian medical journals is recommended.